The Inheritance of Presupposition. - Dinsmore, John, 1949- (Pragmatics & beyond, 1981)
This work presents a procedural account of the so-called 'projection problem' for presupposition. It is assumed that presuppositions embedded in complex sentences are subject to no projection rules or ad-hoc conditions whatever, but are in fact satisfied in appropriate contexts in a completely uniform way. It is demonstrated that the apparent filtering, alteration, or preservation of an embedded presupposition is in every case a logical consequence of a general, independently motivated model of language processing and knowledge representation. It is shown in detail that turning the 'projection.